2017
DOI: 10.3847/1538-4357/aa9062
|View full text |Cite
|
Sign up to set email alerts
|

Inflows, Outflows, and a Giant Donor in the Remarkable Recurrent Nova M31N 2008-12a?—Hubble Space Telescope Photometry of the 2015 Eruption

Abstract: The recurrent nova M31N 2008-12a experiences annual eruptions, contains a near-Chandrasekhar-mass white dwarf, and has the largest mass accretion rate in any nova system. In this paper, we present Hubble Space Telescope (HST) WFC3/UVIS photometry of the late decline of the 2015 eruption. We couple these new data with archival HST observations of the quiescent system and Keck spectroscopy of the 2014 eruption. The late-time photometry reveals a rapid decline to a minimum luminosity state, before a possible reco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 68 publications
0
32
0
Order By: Relevance
“…Recently, Darnley et al (2017) observed M31N 2008-12a in quiescence with HST and concluded that a quiescent disk mass accretion rate is the order of 10 −6 M ⊙ yr −1 , based on their accretion disk model. This large accretion rate, however, clearly contradicts to the current theoretical understanding of nova outbursts because this accretion rate is far above the critical accretion rate for unstable nuclear burning (nova outbursts), several times 10 −7 M ⊙ yr −1 (see, e.g., Nomoto et al 2007;Kato et al 2014).…”
Section: Summary Of Smc N 2016mentioning
confidence: 99%
“…Recently, Darnley et al (2017) observed M31N 2008-12a in quiescence with HST and concluded that a quiescent disk mass accretion rate is the order of 10 −6 M ⊙ yr −1 , based on their accretion disk model. This large accretion rate, however, clearly contradicts to the current theoretical understanding of nova outbursts because this accretion rate is far above the critical accretion rate for unstable nuclear burning (nova outbursts), several times 10 −7 M ⊙ yr −1 (see, e.g., Nomoto et al 2007;Kato et al 2014).…”
Section: Summary Of Smc N 2016mentioning
confidence: 99%
“…Together, this drives eruptions with a mean P rec = 0.99 ± 0.02 yrs [26]. The high accretion rate has been proposed to be due to a Roche-lobe overflowing red giant (or red clump) donor [105]. At present, the composition of the 12a WD has not been confirmed.…”
Section: M31n 2008-12amentioning
confidence: 90%
“…12a is powered by the combination of the most massive WD known (predicted via some models to be 1.38 M ; [58]) accreting, stably, at an exceptionally high rate in the region of 0.6 Ṁ 1.4 × 10 −6 M yr −1 [105]. Together, this drives eruptions with a mean P rec = 0.99 ± 0.02 yrs [26].…”
Section: M31n 2008-12amentioning
confidence: 97%
“…Theoretically, the white dwarf of M31N 2008-12a could reach near-Chandrasekhar-mass through successive eruptions with an initial CO core (Hillman et al 2016). All in all, it is predicted that the M31N 2008-12a white dwarf could reach the Chandrasekhar mass and thus explode as a SNIa in less than 20 kyr (Darnley et al 2017b).…”
Section: Classical Novaementioning
confidence: 98%